Rule - Crownover, Jay (Crownover, Jay. Marked men novel., 2012)
Shaw Landon loved Rule Archer from the moment she laid eyes on him. Rule is everything a straight A pre-med student like Shaw shouldn't want and the only person she's never tried to please. She isn't afraid of his scary piercings and tattoos or his wild attitude. Though she knows that Rule is wrong for her, her heart just won't listen. To a rebel like Rule Archer, Shaw Landon is a stuck-up, perfect princess, and his dead twin brother's girl. She lives by other people's rules; he makes his own. He doesn't have time for a good girl like Shaw, even if she's the only one who can see the person he truly is. But a short skirt, too many birthday cocktails, and spilled secrets lead to a night neither can forget. Now, Shaw and Rule have to figure out how a girl like her and a guy like him are supposed to be together without destroying their love-- or each other.